Blast loading model of the RC column under close-in explosion induced by the double-end-initiation explosive cylinder. (15th November 2018) - Hu, Ye; Chen, Li; Fang, Qin; Xiang, Hengbo
Highlights: Blast tests of double-end-initiated explosive were conducted to reveal mechanism of self-March-reflection. Peak overpressure and impulse exist when D/L of double-end-initiated explosive varies from 0.2 to 0.4. Overpressure and impulse of double-end-initiation are up to 3.5 and 2 times those of single-point-initiation. Applicable loading model under close-in explosion induced by double-end-initiated explosive was developed. Abstract: Charge configuration has a significant impact on the damage of structural components subjected to close-in explosion. To develop a blast loading model on the RC column that can consider the charge shape and detonation configuration, a series of field tests of close-in explosion initiated at two ends of an explosive cylinder (double-end-initiation) were carried out. Highly-centralized blast loading histories were recorded on the mid-span area of the RC column in the field test. A detailed numerical model was developed in the commercial software AUTODYN, which showed a good agreement with the test data. The influences of charge shape, diameter-to-length (D/L) ratio, scaled distance, and detonation position on the overpressure and impulse were discussed. Analytical results reveal that the blast wave propagation and loadings on the column component under close-in explosion are significantly dependent on both shape and initiation-point, which is far different from that of the far-field explosion. The peak reflected overpressure and impulse are up to 3.5 and 2 times larger than those of the center-point-initiated charge, which is actually induced by the self-Mach-reflection of close-in double-end-initiation. An applicable blast loading model under close-in explosion induced by the double-end-initiation explosive cylinder considering D/L ratio and scaled distance was finally established based on the test data and numerical calculations.